The HOPE model for disaster nursing – A systematic literature review. (July 2019) - Hugelius, Karin; Adolfsson, Annsofie
Highlights: This review describes the content, concept and essence in disaster nursing. The HOPE model describes the core element in and essence of disaster nursing. The model can be applied to the response phase in sudden-onset disasters.